What are the macrophages and stellate cells doing in pancreatic adenocarcinoma? - Pandol, Stephen J.; Edderkaoui, Mouad (Frontiers in Physiology, 2015)
Pancreatic ductal adenocarcinoma is a devastating disease characterized by a dense desmoplastic stroma. Chemo- and radio-therapeutic strategies based on targeting cancer cells have failed in improving the outcome of this cancer suggesting important roles for stroma in therapy resistance. Cells in the tumor stroma have been shown to regulate proliferation, resistance to apoptosis and treatments, epithelial to mesenchymal transition (EMT) and stemness of cancer cells. Stellate cells in their activated state have been thought over the past decade to only have tumor promoting roles. However, recent findings suggest that stellate cells may have protective roles as well. The present review highlights the latest findings on the role of two major components of tumor stroma, pancreatic stellate cells and macrophages, in promoting or inhibiting pancreatic cancer, focused on their effects on EMT and cancer stemness.